Analysis of Oil Palm Farmer Households Food Security and Nutrition Based on the Share of Food Expenditures and Energy Consumption - Siti Widiati; Tatang Sutisna; Aulia Ikhsan; Suherman Suherman (Journal of Nutrition Science, 2023)
Compared to farmers who cultivate food and horticultural commodities, oil palm farmers have different business characteristics and incomes. The income of the oil palm farming farmer will affect the food security of the farmer's household family. This study aims to determine the level of food security in the households of smallholder oil palm plantation farmers through a review of the share of food expenditure as well as energy adequacy and minimum energy consumption per capita. The research uses a quantitative descriptive method using structured interview data collection techniques and survey techniques. The respondents were oil palm farmer households who joined oil palm farmer groups in Cipuendeuy Village, Malingping District, Lebak Regency, Banten Province. Quantitative data analysis uses analysis of the Adequacy of Energy Rate (AKE) and Adequacy of Protein (AKP), to analyze the level of household food security. Analysis of the share of food expenditure showed the largest food expenditure of households of oil palm farmers was allocated for grains as much as 31.3%, while the smallest food expenditure was tubers at 1.59%. Based on the share of food expenditure, households of oil palm farmers are in a food secure condition, with 75% of households with a share of food expenditure <60%. The average household energy consumption of oil palm farmers is 1,707.39 kcal per capita/day with a household energy adequacy level of 83.79%. The average protein consumption per capita/day is 80.79 grams with a protein adequacy level of 80.63%. Analysis of the level of food security shows that 41.66% of households are at the level of food secure, 33% are at the level of food insecure, 8.33 are at the level of food vulnerability and 16.66% of households are food insecure.